Methods and results of identification of natural interconnection of grain and an ear during ripening and complete ripeness - A. I. Buriyanov; I. V. Chervyakov; А. А. Kolinko; V. I. Pakhomov; E. V. Ionova; V. F. Khlystunov (Зерновое хозяйство России, 2019)
The new and complete scientific knowledge and information on the physical and mechanical characteristics and morphological traits of the ear of plants are necessary to design and develop less energy-intensive and less injurious threshing methods. The purpose of the research is to establish a change in the coupling strengths of kernels and ear during a ripening period, taking into account the grain moisture and varietal characteristics of winter wheat. It was established that the maximum values of the coupling strengths of spikelet scales and kernels with an ear during the daytime were 17.84 N for the variety “Admiral” and 11.6 N for the variety “Luchezar”. The coupling strengths of kernels and ear and the force of kernel separation effort from the ear significantly depend on: 1) varietal traits of winter wheat (more than in 2 times); 2) humidity of plants during the period of ripening and harvesting time, depending on the variety from 30 to 100%; 3) changes in the moisture content of grain and an ear due to precipitation in 1.5–2.0 times.